Contrasting the primings between English and Chinese: To advance Hoey's theory of lexical priming from the perspective of culture psychology - Wang, Luojia (Frontiers in Psychology, 2022)
The present study demonstrated that Hoey’s promising and serviceable theory could serve as one that can describe and explain similarities and differences exhibited between English and Chinese. Three fundamental concepts as defined in the theory (collocation, colligation, and semantic association) were considered. The combinatory profile showed that: 1)different word choices were primed to constitute to a shared semantic association 2) no unique word combination containing the nodes were found, but high or low frequency use of particular clusters and collocates appearing at both sides to the node occurred; 3) it is claimed that the interpretation and explanation of priming similarities and differences between English and Chinese need to be extended to culture psychology.